Four Sumerian Letter-Orders in Japanese Collections - Yoshikawa, Mamoru
photos and copies UHI (= Iwasaki Collection, Univ. of Hiroshima) 278, UHI 279, NME (= National Museum of Ethnology, Osaka) 94674, NME 94698.